Integrating Passenger Ferry Service with Mass Transit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 102: Integrating Passenger Ferry Service with Mass Transit examines the integration between land- and water-based transit systems and explores successful aspects of seamless integration.
Keywords: Transportation and Infrastructure

Environmental Performance of Tanker Designs in Collision and Grounding: Method for Comparision -- Special Report 259 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2001)
TRB Special Report 259 - Environmental Performance of Tanker Designs in Collision and Grounding: Method for Comparison describes a modeling process for evaluating alternative designs. The process encompasses consideration of the structural deformations from collisions and grounding and the environmental consequences of spills of different sizes, and uses a riskbased approach for comparing designs.Since passage of the Oil Pollution Act (OPA) of 1990 and subsequent decisions of the International Maritime Organization, the world tanker fleet has been evolving to double-hulled designs to reduce the risk of accidental spills. A previous study by the Marine Board, now part of TRB, concluded that the double-hull design had been effective in reducing oil spills (Double-Hull Tanker Legislation: An Assessment of the Oil Pollution Act of 1990, NRC 1998).OPA 1990 was passed because of the 1989 Exxon Valdez oil spill in Prince William Sound. Although the world’s tanker owners have been shifting to double-hull designs, a variety of other hull designs have been proposed that might be as effective and less costly. The U.S. Coast Guard has not been willing to consider such alternatives, in part because of the wording of OPA 1990 and in part because of the difficulty of comparing complex designs.
Keywords: Transportation and Infrastructure

Marine Salvage Capabilities: Responding to Terrorist Attacks in U.S. Ports — Actions to Improve Readiness - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB Conference Proceedings 30: Marine Salvage Capabilities: Responding to Terrorist Attacks in U.S. Ports—Actions to Improve Readiness is the report of the TRB Marine Board Workshop on Marine Salvage Response Capability held on August 5-6, 2003, in Washington, DC. The workshop addressed economic, legal, forensic, environmental, and human casualty issues related to salvage. The report contains a summary of workshop discussions and committee recommendations highlighting important topics and issues associated with marine salvage that warrant further, more detailed inquiry by the responsible federal agencies.
Keywords: Transportation and Infrastructure

U.S. Marine Salvage Assets and Capabilities in a Maritime Disaster - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB Conference Proceedings 45: U.S. Marine Salvage Assets and Capabilities in a Maritime Disaster is the proceedings of a September 2008 workshop that focused on a scenario involving an incident that shuts down the Ports of Los Angeles and Long Beach. The proceedings examine the threat and explore key issues relating to an efficient, effective, and coordinated U.S. salvage industry response to a worst-case marine casualty scenario.
Keywords: Transportation and Infrastructure

Review of U.S. Coast Guard Vessel Stability Regulations - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
On September 12, 2018, TRB released a letter report that reviews regulations and policy documents that establish vessel stability requirements for U.S. Flag vessels. The review, conducted at the request of the U.S. Coast Guard Office of Design and Engineering Standards, considers options to make and keep stability requirements current, align them better with international standards, and improve their consistency, clarity, and usability. In addition to identifying a series of promising options for these purposes, the report makes recommendations to the Coast Guard on coordinating with industry advisory groups and collecting, managing, and analyzing data to inform regulatory decisions.
Keywords: Transportation and Infrastructure

Test Procedures and Classification Criteria for Release of Toxic Gases from Water-Reactive Materials - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Hazardous Materials Cooperative Research Program (HMCRP) Report 13: Test Procedures and Classification Criteria for Release of Toxic Gases from Water-Reactive Materials identifies a procedure for measuring the rate of gas production when a water-reactive material evolving either a flammable gas or a toxic gas is combined with water.
Keywords: Transportation and Infrastructure

Letter Report on a Technical Peer Review of the Buzzards Bay Risk Assessment - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
At the request of the Massachusetts Department of Environmental Protection (MassDEP), the TRB/Marine Board Committee to Review the Buzzards Bay Maritime Risk Assessment has evaluated the methods and conclusions of the Buzzards Bay Risk Assessment (BBRA).The BBRA was originally commissioned by the United States Coast Guard and MassDEP. The committee’s task was to provide an independent technical review of the BBRA focusing on its scope, methods, and supporting data. The committee finds that the choices made in the formulation and execution of the study bring into question the conclusions of the risk assessment on technical grounds and that the ranking of risk mitigation options is not justified and could be reversed with slightly different and more defensible methods or assumptions.
Keywords: Transportation and Infrastructure

Making U.S. Ports Resilient as Part of Extended Intermodal Supply Chains - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 30: Making U.S. Ports Resilient as Part of Extended Intermodal Supply Chains focuses on identifying and elaborating on the steps needed to coordinate freight movements through ports in times of severe stress on existing operating infrastructures and services.This report builds on NCHRP Report 732: Methodologies to Estimate the Economic Impacts of Disruptions to the Goods Movement System to provide a set of high-level guidelines to help seaport authorities with minimizing lost throughput capacity resulting from a major disruption.
Keywords: Transportation and Infrastructure

Offshore Wind Energy Projects: Summary of a Workshop - Transportation Research Board (The National Academies Press, 2011)
TRB Conference Proceedings on the Web 4: Offshore Wind Energy Projects: Summary of a Workshop summarizes a March 2010 workshop held in Washington, D.C., that examined the processes use by the former Minerals Management Service (MMS) for selecting and managing certified verification agents (CVAs) and for identifying appropriate standards for assuring good engineering judgment and practice; for reviewing and approving designs, fabrications, and installations; and for determining acceptable qualifications and role for a CVA associated with nonhydrokinetic offshore renewable energy projects.
Keywords: Transportation and Infrastructure

Offshore Wind Energy Projects: Summary of a Workshop - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB Conference Proceedings on the Web 4: Offshore Wind Energy Projects: Summary of a Workshop summarizes a March 2010 workshop held in Washington, D.C., that examined the processes use by the former Minerals Management Service (MMS) for selecting and managing certified verification agents (CVAs) and for identifying appropriate standards for assuring good engineering judgment and practice; for reviewing and approving designs, fabrications, and installations; and for determining acceptable qualifications and role for a CVA associated with nonhydrokinetic offshore renewable energy projects.
Keywords: Transportation and Infrastructure

North American Marine Highways - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 5: North American Marine Highways explores the potential for moving intermodal containers on chassis, non-containerized trailers, or rail cars on marine highways in North America. The report includes an assessment of the conditions for feasibility; an analysis of the economic, technical, regulatory, and logistical barriers inhibiting greater use of the marine highway system; and potential ways to eliminate these barriers.
Keywords: Transportation and Infrastructure

Security Measures for Ferry Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB's Transit Cooperative Research Program (TCRP) Report 86: Public Transportation Security, Volume 11: Security Measures for Ferry Systems is designed to assist U.S. ferry system operators in evaluating and selecting general security measures (GSM) for their operations consistent with the National Incident Management System.The seven-step GSM evaluation process and the description of the characteristics of the U.S. ferry system in TCRP Report 86, vol. 11 are supplemented by an Excel tool for applying the seven-step GSM evaluation process.The TCRP Report 86: Public Transportation Security series assembles relevant information into single, concise volumes, each pertaining to a specific security problem and closely related issues. These volumes focus on the concerns that transit agencies are addressing when developing programs in response to the terrorist attacks of September 11, 2001, and the anthrax attacks that followed. Future volumes of the report will be issued as they are completed.
Keywords: Transportation and Infrastructure

Multimodal Freight Transportation Within the Great Lakes--Saint Lawrence Basin - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 17: Multimodal Freight Transportation Within the Great Lakes--Saint Lawrence Basin describes the current multimodal freight transportation system within this bi-national region--Minnesota, Wisconsin, Michigan, Illinois, Indiana, Ohio, Pennsylvania, New York, Ontario, and Quebec--and its importance to regional, United States, and Canadian economies.The report also analyses the system’s overall performance and related opportunities and constraints to improving performance and to meet projected freight flows.The report includes an analysis of each mode’s capacity and the major commodities each of them moves; the barriers and constraints that impact each mode’s ability to move cargo; the performance implications in terms of major commodity supply chains (coal, automotive parts and machinery, containerized consumer goods, grains, and iron ore); and a strategic freight planning process for multimodal transport chain performance going forward.Errata - In September 2012 the PDF version of the report was updated to include two authors that were inadvertently omitted in the print versions of the report.
Keywords: Transportation and Infrastructure

Enhancing Sleep Efficiency on Vessels in the Tug/Towboat/Barge Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Freight Research Program (NCFRP) Report 36: Enhancing Sleep Efficiency on Vessels in the Tug/Towboat/Barge Industry provides best practices to improve an operator's sleep and reduce operator fatigue in the United States inland waterway industry, including the use of anchor-sleep/nap-sleep strategies.NCFRP Report 36 identifies and describes the metrics that could be used to evaluate current operational interventions (e.g., educational materials and programs; noise abatement; sleep disorders screening, especially sleep apnea; wellness and nutritional programs) for their effectiveness in improving sleep efficiency on tugs/towboats/barges; evaluates the use of anchor-sleep/nap-sleep strategies on sleep behavior among personnel in the inland waterway industry; and identifies barriers that inhibit waterway personnel from adopting good sleep management practices and propose ways to overcome the barriers.The report also develops a list of best practices that could be implemented by the waterway industry, companies, crews, or individuals to enhance sleep efficiency; and includes a compendium of best practices for enhancing sleep efficiency in the U.S. inland waterway industry.
Keywords: Transportation and Infrastructure

Guidelines for Ferry Transportation Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Transit Cooperative Research Program (TCRP) Report 152: Guidelines for Ferry Transportation Services examines the history and characteristics of ferry systems throughout North America and offers guidelines for planning, marketing, operating, and managing a ferry system as a component of an overall transportation network.The report also explores the potential benefits of and impediments to ferry transportation services and identifies potential planning, operational, and management benchmarks.
Keywords: Transportation and Infrastructure

Leveraging Unmanned Systems for Coast Guard Missions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
As unmanned systems (UxS) continue to develop and be used by other military services and federal agencies, the U.S. Coast Guard should proceed more aggressively and deliberately in taking advantage of UxS advancements, says a new congressionally mandated report from the National Academies of Sciences, Engineering, and Medicine.The Coast Guard should also produce a high-level strategy with critical goals and actionable steps toward fully utilizing UxS technology, according to TRB Special Report 335: Leveraging Unmanned Systems for Coast Guard Missions.UxS technologies include aerial, surface, and underwater vehicles with no human occupants; vehicles that may have a crew but with some level of remote control; and systems that are not vehicles.As one of the country’s six military services, the Coast Guard also serves as a first responder, law enforcement agency, maritime regulator, and member of the intelligence community. Despite multiple initiatives to explore and assess the applicability of UxS to these areas, the Coast Guard lacks a formal means for identifying, investigating, and integrating systems. Meanwhile, UxS technological advancements continue to accelerate, driven by both commercial and military demands.
Keywords: Transportation and Infrastructure

Feasibility of a Consolidated Security Credential for Persons Who Transport Hazardous Materials - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Hazardous Materials Cooperative Research Program (HMCRP) Report 6: Feasibility of a Consolidated Security Credential for Persons Who Transport Hazardous Materials discusses the feasibility of consolidating several existing security credentials, which are necessary under current regulations and policies, into one credential for all transportation modes.The report evaluates the credentialing system to identify duplicative elements and redundant costs and describes the acquisition process, the application elements, and the physical characteristics for each identified credential. In addition, the report identifies the elements of the vetting processes for each credential. The report includes an examination of four options for consolidation, which provides insight into the basic elements of a universally recognized security credential for HazMat transportation workers.HMCRP Report 6 also identifies key challenges for consolidation of security credentials, such as impetus and authority, organizational climate, financing, risk, and technological trending.An alternative method of consolidating background checks is identified as a possible intermediate solution for removing duplicative processes and redundant costs.A PowerPoint presentation, which summarizes the report process and conclusions, is available for download.
Keywords: Transportation and Infrastructure

Guidelines for Transportation Emergency Training Exercises - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 525: Surface Transportation Security and TRB’s Transit Cooperative Research Program (TCRP) Report 86: Public Transportation Security series publications have jointly published Guidelines for Transportation Emergency Training Exercises. The report is Volume 9 in each series. The report is designed to assist transportation agencies in developing drills and exercises in alignment with the National Incident Management System. The report describes the process of emergency exercise development, implementation, and evaluation. In addition, the available literature and materials to support transportation agencies such as state departments of transportation, traffic management centers, and public transportation systems are described.NCHRP Report 525: Surface Transportation Security is a series in which relevant information is assembled into single, concise volumes—each pertaining to a specific security problem and closely related issues. The volumes focus on the concerns that transportation agencies are addressing when developing programs in response to the terrorist attacks of September 11, 2001, and the anthrax attacks that followed. Future volumes of the report will be issued as they are completed.
Keywords: Transportation and Infrastructure

Quantitative Procedures for Designing and Operating Ferry Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Ferry transportation services play an important role in regional transportation—providing additional transit capacity to transportation networks and serving as a lifeline for many geographically-isolated communities.The TRB Transit Cooperative Research Program's TCRP Research Report 238: Quantitative Procedures for Designing and Operating Ferry Services presents guidance for scheduled and fixed-route ferry transit services and facilities that serve passengers as well as passengers and vehicles. Guidance focuses on defining the capacity of a ferry system and understanding capacity challenges, and includes quantitative procedures for designing and operating ferry services.
Keywords: Transportation and Infrastructure

Evaluation of the Use of Electronic Shipping Papers for Hazardous Materials Shipments - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Hazardous Materials Cooperative Research Program (HMCRP) Report 8: Evaluation of the Use of Electronic Shipping Papers for Hazardous Materials Shipments examines the challenges of advancing the use of electronic shipping papers as an alternative to the current paper-based hazardous materials communication system.
Keywords: Transportation and Infrastructure